TINJAUAN YURIDIS HAK WARIS ANAK TERHADAP PEMBATALAN PERKAWINAN MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - maya yunita (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT            Marriage is one of the social events that would cause legal consequences for prospective husbands and wives, children or any third party . Act No. 1 of 1974 article 22 on marriage say that marriage can be canceled if the parties do not meet requirements that have been determined to enter into marriage.            The purpose of this paper is divided into 2 (two), namely: general purpose and special purpose. The general aim in writing this paper are: First, to qualify and academic work to earn a law degree in Faculty of Law, University August 17, 1945. Second, is one form of application of knowledge that have been acquired during the course in life community. Third, to contribute ideas that benefit society, students of the Faculty of Law, University August 17, 1945 and alamamater. While the specific objectives: First, to know and understand the legal status of children whose parents canceled the marriage. Second, to know and understand the legal consequences of the cancellation of the marriage of husband and wife for the rights of the child. Type in the writing of this thesis is a normative juridical approach while the problem of using the Act and conceptual. Methods of collecting legal material used is a source of primary legal materials, sources of secondary law, chapter discussion, will discuss the two (2) what is in the formulation of the problem.            Children born out of wedlock still have a clear legal status as a legitimate child of the parents canceled the wedding was canceled . Annulment both parents do not remove or do not result in the loss of its status . So in this case the children born of the marriage canceled remain entitled to inheritance rights against parents. Keywords : Marriage Abrogation, Inheritance rights of the Child and Child Protection. Keywords        :   Implementation, Regulation Election Commission, voters list, the General Election Commission